Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

Molecular Mechanisms Underlying Neuroprotective Effect of Intranasal Administration of Human Hsp70 in Mouse Model of Alzheimer's Disease. - Evgen'ev, Michail B; Krasnov, George S; Nesterova, Inna V; Garbuz, David G; Karpov, Vadim L; Morozov, Alexey V; Snezhkina, Anastasiya V; Samokhin, Alexander N; Sergeev, Alexander; Kulikov, Alexei M; Bobkova, Natalia V (J Alzheimers Dis, 2017)
Heat shock protein 70, encoded by the HSPA1A gene in humans, is a key component of the machinery that protects neuronal cells from various stress conditions and whose production significantly declines during the course of aging and as a result of several neurodegenerative diseases. Herein, we investigated whether sub-chronic intranasal administration of exogenous Hsp70 (eHsp70) exerts a neuroprotective effect on the temporal cortex and areas of the hippocampus in transgenic 5XFAD mice, a model of Alzheimer's disease. The quantitative analysis of neuronal pathologies in the compared groups, transgenic (Tg) versus non-transgenic (nTg), revealed high level of abnormalities in the brains of transgenic mice. Treatment with human recombinant Hsp70 had profound rejuvenation effect on both neuronal morphology and functional state in the temporal cortex and hippocampal regions in transgenic mice. Hsp70 administration had a smaller, but still significant, effect on the functional state of neurons in non-transgenic mice as well. Using deep sequencing, we identified multiple differentially expressed genes (DEGs) in the hippocampus of transgenic and non-transgenic mice. Furthermore, this analysis demonstrated that eHsp70 administration strongly modulates the spectrum of DEGs in transgenic animals, reverting to a pattern similar to that observed in non-transgenic age-matched mice, which included upregulation of genes responsible for amine transport, transmission of nerve impulses and other pathways that are impaired in 5XFAD mice. Overall, our data indicate that Hsp70 treatment may be an effective therapeutic against old age diseases of the Alzheimer's type.